2018
DOI: 10.1007/978-1-4939-7816-8_31
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Amyloid-β Plaques and Autofluorescent Lipofuscin Aggregates in Alzheimer’s Disease Brain: A Confocal Microscopy Approach

Abstract: The study of brain pathology by fluorescence microscopy finds in the autofluorescence of the tissue an additional difficulty for the recognition of markers of interest. In particular, in the immunofluorescence study of brains from Alzheimer's disease (AD) patients, several approaches have been attempted to eliminate or mask the presence of autofluorescent aggregates. In the present work, we propose a method to characterize by fluorescent microscopy senile plaques discriminating them from autofluorescent aggreg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 18 publications
0
8
0
Order By: Relevance
“…For example, DNA probes emitting in the far-red range can be combined with the detection of LF in both green and red channels (Zheng et al, 2010 ). Recently, we have developed a method based on channel filtering of confocal microscopy to identify and discriminate LF autofluorescence signals from the specific ones, such as amyloid plaques in the AD brain (see Figure 1 ) (Kun et al, 2018 ).…”
Section: Lipofuscin Composition and Distributionmentioning
confidence: 99%
“…For example, DNA probes emitting in the far-red range can be combined with the detection of LF in both green and red channels (Zheng et al, 2010 ). Recently, we have developed a method based on channel filtering of confocal microscopy to identify and discriminate LF autofluorescence signals from the specific ones, such as amyloid plaques in the AD brain (see Figure 1 ) (Kun et al, 2018 ).…”
Section: Lipofuscin Composition and Distributionmentioning
confidence: 99%
“…The hypothesis of free radical damage in AD postulates that (Cabungcal et al, 2013) the body's defense systems are weakened with disease progression, causing the accumulation of a pathologically high level of free radicals, which react with unsaturated fatty acids in the cell membrane to form lipid peroxides such as malondialdehyde. Malondialdehyde combines with proteins, nucleic acids, and other biological macromolecules to form insoluble lipofuscin deposits in cells (Kun et al, 2018). Lipofuscin can damage cell structure, disrupt cell metabolism, accelerate cell senescence and death, as well as affect learning and memory (Giaccone et al, 2011;Kwon et al, 2016).…”
Section: The Ecm Resists Oxidative Stress and Reduces Ad Damagementioning
confidence: 99%
“…One additional interesting observation was the increased presence of autofluorescent aggregates as ageing progressed. These aggregates resemble lipofuscin in appearance and properties (wide fluorescence emission range; Fahim & Robbins, 1982; Kun et al., 2018). It has previously been reported that the appearance of lipofuscin is associated with ageing (Terman & Brunk, 1998, 2004, 2005; Terman et al., 2010).…”
Section: Discussionmentioning
confidence: 99%